Microservices implementation using Rest API for MSMEs based on Raspberry PI - Ningsih, Norma; Muna, Nailul; Nadziroh, Faridatun (Sistemasi: Jurnal Sistem Informasi, 2024)
Micro, Small and Medium Enterprises (MSMEs) are business activities that are able to expand employment opportunities and provide broad economic services to the community. The role of digital technology has increased significantly to assist activities and transactions via the internet, whether accessed via web, mobile or desktop technology. In carrying out their business processes, MSMEs need access to other services such as banks for payment processing. Apart from that, multiplatform applications are needed to make it easier for customers to access the services provided by MSMEs. Based on the above needs, an MSME back-end application was developed using the REST API web service architecture which runs on a Raspberry PI which functions as a server for computing and data storage processes. The system development method uses the waterfall method with the Golang programming language. The system developed has been tested using the Insomnia tool for the REST API that has been created and the Vegeta tool as HTTP load testing. The results obtained in this test using the POST and GET methods were that for a number of requests of 25 and 150 transactions were 100% successful, however for a number of requests of 500 there were 32% failed transactions. Power consumption increases according to the number of accesses to the system with the average value in each scenario being 4.24, 4.54, 4.7 watts.